Rosuvastatin Attenuated Elastic Fiber Degradation in Chronic Obstructive Pulmonary Disease Sprague-Dawley Rats - Sabirin, Rahmaningsih Mara; -, Prasetyastuti; Agustiningsih, Denny (Jurnal Kedokteran Brawijaya, 2019)
Chronic obstructive pulmonary disease (COPD) is an incurable disease which causes disability and death. The main pathogenesis of COPD is oxidative stress due to cigarette smoke which initiates various reactions and lead to lung elastic fibers destruction. Statins are known to have antioxidant effects and reduce mortality in COPD. We studied the effects of cigarette smoke exposure cessation and rosuvastatin on oxidative stress and the level of elastic fiber destruction in COPD model rats. Thirty 10-week old male Sprague-Dawley rats were divided into 2 groups: Control (n=6, did not received fumigation nor treatment) and Smoking (n=24, received fumigation for 70 days) groups. Afterwards, the smoking group was divided into 4 groups: Sham, R2, R5,R10, and received 0.9% NaCl, 2.5, 5 and 10 mg/kg/day of rosuvastatin, respectively. Examination of malondialdehyde (MDA) and desmosine serum were conducted to measure oxidative stress and elastic fiber degradation level, respectively. After smoke exposure, MDA and desmosine levels of COPD rats were found to be significantly higher (p=0.000 and 0.000) than controls. The MDA level in Sham, R2, R5 and R10 groups decreased significantly after therapy (p=0.000; 0.033; 0.015; 0.002). However, the post-treatment desmosine level was increase significantly in Sham and R2 groups (p=0.006 dan 0.012) and insignificantly (p=0.117 dan 0.278) in the R5 and R10 groups. It can be concluded that the cessation of exposure to cigarette smoke can reduce oxidative stress, but not elastic degradation process. The administration of rosuvastatin of 5 or 10 mg/kg/day attenuated elastic degradation process.